PEMEROLEHAN KOSAKATA BAHASA INDONESIA ANAK USIA PRASEKOLAH DI KECAMATAN BARRU: KAJIAN PSIKOLINGUISTIK - Hasniar Hasniar (JURNAL ILMU BUDAYA, 2020)
Family environment and social environment influence the process of acquiring Indonesian vocabulary for preschool children. This study aims to determine the vocabulary mastery of Indonesian preschool children. The case study of this research was located in Barru Regency. The research object studied was the mastery of the Indonesian language, the type of word class, and the factors that influenced it. The method used is a qualitative descriptive research method. The results of this study include the form of acquisition of Indonesian preschool children which consists of 4 words, phrases, clauses, and sentences. The dominant type of word class is the object vocabulary category (noun), and four factors affect the vocabulary mastery of Indonesian preschool children in Barru Regency, namely environmental factors, facilities, and children's health. The family environment and the environment in which preschool children generally speak Bugis language affect the Bugis dialect of preschool children in Indonesian.